2011
DOI: 10.4103/0974-2069.79632
|View full text |Cite
|
Sign up to set email alerts
|

Kodamaea ohmeri tricuspid valve endocarditis with right ventricular inflow obstruction in a neonate with structurally normal heart

Abstract: The yeast Kodamaea (Pichia) ohmeri is a rare human pathogen with infrequent report of neonatal infection. Native valve endocarditis by Kodamaea ohmeri is extremely rare. The current case report describes a case of fatal nosocomial native valve endocarditis without any structural heart defects in a 40dayold baby. The patient was referred to our institute after having ICU stay of 18 days in another hospital for necrotizing enterocolitis and was found to have obstructive tricuspid valve mass and fungemia with Kod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…The infection was often serious and fatal (attributable mortality 31.8%). Kodamaea ohmeri is rarely reported to cause human infection . Before the present report, only 39 cases of K. ohmeri infection had been reported.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The infection was often serious and fatal (attributable mortality 31.8%). Kodamaea ohmeri is rarely reported to cause human infection . Before the present report, only 39 cases of K. ohmeri infection had been reported.…”
Section: Discussionmentioning
confidence: 70%
“…The clinical importance of other Kodamaea species (K. anthrophila, K. kakaduensis, K. laetipori K. nitidulidarum) is not known [10]. Kodamaea ohmeri is reported to cause high mortality (50%) in paediatric populations [11][12][13][14][15][16][17][18][19][20][21]. From our tertiary care centre with 1740 beds we report a very high incidence of fungaemia (300-500 cases every year) and C. tropicalis is the commonest isolate [8,[22][23][24].…”
Section: Introductionmentioning
confidence: 91%
“…No additional studies were found during the hand‐screening of the included articles' references. Finally, 35 met the present study's inclusion criteria 3,4,7–39 . The review process is graphically presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Introduction Kodamaea (Pichia) ohmeri is a rarely occurring yeast that has recently been identified as a cause of fungaemia, endocarditis, cellulitis, funguria and peritonitis in neonates and children [83][84][85][86][87], and in both immunocompromised [88][89][90][91] and immunocompetent [92,93] [94] by traditional methods and molecular identification is mandatory.…”
Section: Kodamaea Ohmerimentioning
confidence: 99%
“…Kodamaea ( Pichia ) ohmeri is a rarely occurring yeast that has recently been identified as a cause of fungaemia, endocarditis, cellulitis, funguria and peritonitis in neonates and children , and in both immunocompromised and immunocompetent adult patients. The anamorphic state is Candida guilliermondii var .…”
Section: Introductionmentioning
confidence: 99%